Frontispiece: Presodiation Strategies for the Promotion of Sodium‐Based Energy Storage Systems. Issue 65 (24th November 2021) - Song, Zirui; Zou, Kangyu; Xiao, Xuhuan; Deng, Xinglan; Li, Shuo; Hou, Hongshuai; Lou, Xiaoming; Zou, Guoqiang; Ji, Xiaobo
Abstract : Presodiation, known as pre‐doping of sodium ions, represents the addition of sodium sources to ensure adequate sodium content in the sodium‐based energy storage systems. In this minireview, various presodiation strategies are divided into following categories: Electrochemical, Additives, Direct contact, Alternatives of Na and Novel methods. In addition, multiple functions of presodiation are clarified, such as compensating for sodium loss, addressing safety issue, enhancing energy density and so on, aiming to promote the development of Na‐based energy storage systems. For more information, see the Minireview by X. Lou, G. Zou, and X. Ji et al. on page ff16082 .